(untitled) (International Journal of Architecture and Urbanism, 2024)
Lake Siombak area, located in North Sumatra, Medan City, Medan Marelan District, and Paya Pasir Village, has potential for development as stipulated in the RTRW regional regulation. But in the area, there are no tourism facilities such as lodging or waterside recreation areas with lakes. Judging from the existing potential, what are the criteria for facility tourism with the concept of lakeside architecture? As well as how to design a building with a lakeside architectural concept? This thesis will be answered with a qualitative descriptive method, namely, a method that uses the method for collecting data, presenting, comparing, and analyzing data, as well as conducting a field survey. The concept is applied by considering the orientation towards the lake, making openings towards the lake, making the lake the main view, and using materials and tourist facilities that can best support the design of resorts in the Lake Siombak area. In addition to supporting amenities like lakeside recreation areas, theme parks, barbecue areas, and a jetty, the design’s dynamic building shape is oriented towards the lake, has the best view from every angle, and uses more natural materials so that the building can adapt to the surrounding area.